Emptying lakes, filling up seas: hydroelectric dams and the ambivalences of development in late Soviet Central Asia - Florin, Moritz (Central Asian Survey, 2019)
In the late Soviet Union, large-scale projects such as the Toktogul Dam in the Kyrgyz Soviet Republic were promoted as emblems of the Soviet model of development in Asia. While Central Asian politicians and intellectuals usually tuned in to the enthusiasm, the construction also revealed different opinions about the precise direction and goals of Soviet development. Large-scale investments became focal points of political and intellectual debates; they not only helped bind the periphery closer to the Soviet centre, but also revealed the different economic, political and cultural priorities of the regional, republican and union-wide actors. The construction of dams and reservoirs eventually triggered conflicts between the republics and laid the foundation for an anti-colonial critique of the late Soviet state.
CRIS-Team Scopus Importer:2019-06-21
Keywords: development; ecocriticism; hydroelectricity; Kyrgyzstan; late Soviet Union; resettlement